2000
DOI: 10.1021/ef000097a
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Kinetic Constants of a Five-Lump Model for Fluid Catalytic Cracking Process Using Simpler Sub-models

Abstract: A new sequential method to estimate rate constants in complex kinetic models is proposed. This method reduces the number of parameters to be estimated simultaneously. A five-lump kinetic model for the catalytic cracking process was selected in order to apply the proposed methodology. The kinetic parameters of this model were determined by using successively non linear estimation with various three-and four-lump kinetic models. Experimental data obtained in a MAT reactor using three gas oils and a commercial eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Ancheyta et al [17,[36][37][38] employed a laboratory fixed-bed reactor described by ASTM D 3907-92 (microactivity test, MAT) to investigate the catalytic cracking of VGOs. They proposed five lump kinetic models [37,38] and found that the second-order kinetic expression best described the catalytic cracking of gas oils.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ancheyta et al [17,[36][37][38] employed a laboratory fixed-bed reactor described by ASTM D 3907-92 (microactivity test, MAT) to investigate the catalytic cracking of VGOs. They proposed five lump kinetic models [37,38] and found that the second-order kinetic expression best described the catalytic cracking of gas oils.…”
Section: Resultsmentioning
confidence: 99%
“…Ancheyta et al [17,[36][37][38] employed a laboratory fixed-bed reactor described by ASTM D 3907-92 (microactivity test, MAT) to investigate the catalytic cracking of VGOs. They proposed five lump kinetic models [37,38] and found that the second-order kinetic expression best described the catalytic cracking of gas oils. They also established that the kinetic parameters were correlated as a function of carbon distribution (C A and C P /C N ratio) obtained by the n-d-M method (ASTM D3238) and the total sulfur (St) and nitrogen (Nt) contents for the catalytic cracking of six gas oils [17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is expected in this work that the upper and lower limits for the activation energy, heat of reaction and frequency factors should be within the existing range. The values from the literature are: activation energy (31,923-57,278.96 kJ/kg mol) [43,44] and (31,820-66,570 kJ/kg mol) [19], heat of reaction (195-745 kJ/kg) and frequency factor (0.000629-1457.5 s −1 ) [19]. The upper and lower limits are opened further wide on the gPROMS parameter estimation framework to allow the software make the best estimates.…”
Section: Givenmentioning
confidence: 99%
“…On the other hand, semiempirical models, which have simple calculations, cannot be used for these reactions. , Therefore, the lumping methodology has been utilized for the complex reaction systems involved in the catalytic cracking process. In this way, similar components according to their boiling point and molecular characteristics are categorized into several cuts or lumps. , Many lumping models for catalytic cracking have been proposed and classified into two groups: (1) components are lumped based on the molecular structure characteristics of hydrocarbons, such as the four-lump kinetic model of Ojong et al, the seven-lump kinetic model of Fukuyama and Terai, the eight-lump model of Wang et al., the twelve-lump model of Zong et al., and the seventeen-lump model of Singh et al; (2) components are lumped based on the boiling point or molecular weight range, such as the four-lump kinetic model of Dave et al, Ancheyta-Juárez et al, and by Shayegh et al, the five-lump kinetic model of Sánchez et al and Ancheyta-Juárez et al, , the six-lump model of Ancheyta and Sotelo, Sadighi et al, Xiong et al, John et al, and by Seyed Asaee et al, the seven-lump model of Heydari, and the eight-lump model of Sani et al, You et al, and Sun et al In addition to these two types, in several studies, lumped kinetic models based on the chemical structure and boiling points are mixed, such as the ten-lump kinetic model proposed by Du et al and the nine-lump model by Ebrahimi et al and by Zhang et al Generally, the type of model is selected based on the purpose of the research.…”
Section: Introductionmentioning
confidence: 99%